CHEMICAL QUALITY OF RICE STRAW SILAGE SUPPLEMENTED BY DIFFERENT TYPE OF LEGUMES - R., Ramadhan; Cakra, I G. L. O.; Mariani, N. P. (Jurnal Peternakan Tropika, 2022)
The study aims to determine the chesmistry quality of rice straw silage supplemented by different type of legumes. This research was conducted from November to December at the Sesetan Farm and silage analysis was carried out at the Laboratory of Animal Nutrition and Forage, Faculty of Animal Husbandry, Udayana University. The design in the study was complete random concoction with five treatments and four replications. The five treatments were: 90% rice straw + 5% pollard + 5% molase (P0) “control”, 60% rice straw + 5% pollard + 5% molase + 30% Calliandra calothyrsus (P1), 60% rice straw + 5% pollard + 5% molase + 30% Gliricidia sepium (P2), 60% rice straw + 5% pollard + 5% molase + 30% Indigofera zollingeriana (P3), 60% rice straw + 5% pollard + 5% molase + 30% Sesbania grandiflora (P4). The variables observed were dry matter, crude protein, crude fiber, crude fat, ash, and organic matter. The results showed, the highest crude protein and the lowest crude fiber value was P2 treatment 15,58% and 24,81%. The highest organic matter and the lowest ash value was P1 treament 86,07% and 13,93%. The highest crude fat and the lowest dry matter value was P4 treatment 15,88% and 84,96%. From the results of the study it can be concluded that rice straw silage supplemented by Gliricidia sepium produced the best chemical quality by having the highest crude protein. Keywords: rice straw, silage chemical quality, legume